Modelling Interfaces in Thin-Film Photovoltaic Devices - Jones, Michael D. K.; Dawson, James A.; Campbell, Stephen; Barrioz, Vincent; Whalley, Lucy D.; Qu, Yongtao (Frontiers in Chemistry, 2022)
Developing effective device architectures for energy technologies---such as solar cells, rechargeable batteries or fuel cells---does not only depend on the performance of a single material, but on the performance of multiple materials interfaced together. A key part of this is understanding the behaviour at the interfaces between these materials. In the context of a solar cell, efficient charge transport across the interface is a pre-requisite for devices with high conversion efficiencies. There are several methods that can be used to simulate interfaces, each with an in-built set of approximations, limitations and length-scales. These methods range from those that consider only composition e.g. data-driven approaches) to continuum device models e.g. drift-diffusion models using the Poisson equation) and ab-initio atomistic models e.g. density functional theory). Here is an introduction to interface models at various levels of theory, highlighting the capabilities and limitations of each. In addition, a discussion of several of the various physical and chemical processes at a heterojunction interface, highlighting the complex nature of the problem and the challenges it presents for theory and simulation.